2019
DOI: 10.1001/jamanetworkopen.2019.6803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-term Survival Benefits in Trials of Immune Checkpoint Inhibitor vs Non–Immune Checkpoint Inhibitor Anticancer Agents Using ASCO Value Framework and ESMO Magnitude of Clinical Benefit Scale

Abstract: IMPORTANCE Recently, anticancer agents have generated excitement owing to their capacity to preserve long-term durable survival in some patients who are represented by a tail of the survival curve. However, because traditional measures of clinical benefit may not accurately capture durable survival, amendments to various valuation frameworks have been proposed to capture this benefit. OBJECTIVES To determine how frequently immune checkpoint inhibitor (ICI) anticancer agents vs non-ICI anticancer agents display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In addition, the inherent interrater variability is a potential limitation within ASCO-VF scoring, as with any measurement tool. Nevertheless, after factoring previous literature into account, 6,15,16 we found that only a small number of cases differed, and our final findings remained the same after sensitivity analysis (results not shown). Finally, because only a small number of drugs approved under the accelerated approval pathway were included, the present study could not draw strong conclusions analyzing this subgroup.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the inherent interrater variability is a potential limitation within ASCO-VF scoring, as with any measurement tool. Nevertheless, after factoring previous literature into account, 6,15,16 we found that only a small number of cases differed, and our final findings remained the same after sensitivity analysis (results not shown). Finally, because only a small number of drugs approved under the accelerated approval pathway were included, the present study could not draw strong conclusions analyzing this subgroup.…”
Section: Discussionsupporting
confidence: 57%
“…19 The remaining scores were completed by 2 independent reviewers, with consultation of a third reviewer when necessary, with experience applying the valuation frameworks. 6 , 27 , 31 , 32 , 33 , 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of ASCO's value framework with other scoring systems like the European Society of Medical Oncology-Magnitude of Clinical Benefit Scale, which credits therapies demonstrating plateauing survival curves, revealed that very few (,3%) cancer treatments fulfilled the European Society of Medical Oncology criterion to receive points for long-term survival. 22,23 Furthermore, researchers outside of health economics have broadly defined the concept of hope to represent authentic spirit and comfort, 24 and they have accepted hope as an effective coping strategy that improves quality of life during end-of-life care. 25 In addition, we acknowledge that there may be other explanations for the choice patterns we have observed.…”
Section: Discussionmentioning
confidence: 99%